2013
DOI: 10.1039/c3cp51904j
|View full text |Cite
|
Sign up to set email alerts
|

Electron correlation and relativistic effects in the secondary NMR isotope shifts of CSe2

Abstract: Secondary isotope effects on nuclear shielding provide an experimentally well-defined reference point of quantum-chemical methodology. We carry out a quantum-mechanical treatment of thermal rovibrational motion in the linear CSe2 molecule and combine it with relativistic modeling of (77)Se and (13)C nuclear magnetic shieldings. The effects of electron correlation are studied at nonrelativistic (NR) ab initio and both NR and relativistic density functional theory (DFT) levels. Fully relativistic 4-component Dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
(136 reference statements)
1
5
0
Order By: Relevance
“…Even a relatively “light” HA like sulfur can induce an overall δ SO shielding of −8 ppm at the adjacent 13 C nuclei of CS 2 via the CS double bonds. , In addition to the two factors mentioned above, a large carbon 2s character in the C–S bonds (formal sp 2 hybridization) also aids this shielding. A thorough study of the SO-HALA effects in heavy chalcogen complexes at the Coupled-Cluster with Single and Double and Perturbative Triple excitations CCSD­(T) and Breit-Pauli Perturbation Theory (BPPT) levels of theory was performed to evaluate secondary isotope effects on nuclear shielding in CSe 2 . , …”
Section: Trends In So-hala Shifts Across the Periodic Tablesupporting
confidence: 52%
“…Even a relatively “light” HA like sulfur can induce an overall δ SO shielding of −8 ppm at the adjacent 13 C nuclei of CS 2 via the CS double bonds. , In addition to the two factors mentioned above, a large carbon 2s character in the C–S bonds (formal sp 2 hybridization) also aids this shielding. A thorough study of the SO-HALA effects in heavy chalcogen complexes at the Coupled-Cluster with Single and Double and Perturbative Triple excitations CCSD­(T) and Breit-Pauli Perturbation Theory (BPPT) levels of theory was performed to evaluate secondary isotope effects on nuclear shielding in CSe 2 . , …”
Section: Trends In So-hala Shifts Across the Periodic Tablesupporting
confidence: 52%
“…[61] This idea was successfully applied in calculations of NMR parameters by numerous authors. [62][63][64] We understand that the idea does not reflect the true nature, but our previous calculations of SSCCs involving either selenium nuclei or tellurium nuclei [28,[65][66][67] have also indicated that this assumption leads to satisfactory estimations. To provide a rather reliable description of the electron correlation, we have used, as a starting point, the combination of the SOPPA (CC2) method for the evaluation of 1 J( 77 Se, 31 P) and 1 J( 125 Te, 31 P) SSCCs at the nonrelativistic level of theory and the fourcomponent DFT-KT1 approach for the relativistic corrections.…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…The reason for such small relativistic effects on the heavy 77 Se nucleus could be in the significant mutual cancellation of the different relativistic influences on the nuclear shielding tensor, which were recently discussed in ref. [49].…”
Section: Heavy-element Moleculesmentioning
confidence: 95%